Filmes e educação: o caminho do sensível na construção de conhecimento - Pena, Saulo de Oliveira (2020)
This qualitative research looks at the relationship between education and sensitivity through the reasons why teachers base their practices on films. Structured in the bibliographic and empirical stages, when interviewing 10 teachers from the São Paulo municipal education system, with the objective of investigating whether the path of the sensitive appears in the intentions of these professionals and analyzing how they perceive the reaction of their students. Throughout the course, we sought to understand the relationship between knowing and the way of feeling, from the perspective of the teacher who accesses the video or multipurpose room in the school and even the one who takes filmic plots into the classroom. The starting point for this dissertation was due to concerns about the presence of film narratives at school. The perspective adopted is that they appear as a way to humanize relations with knowledge. The research will have as a theoretical reference the complex thinking of Edgar Morin, from reflections on the aesthetic state, investigating how feeling contributes to school education. The magic of moving images appears, in this perspective, as a “life experience” that presents the student with values, customs and behaviors, which represent, according to the author, the Culture of Humanities. In the methodological trajectory, academic studies presented that configure the scope of this dissertation and indicate the possibilities of approaching it, which is a recurring theme in academic research on education. The empirical stage carried out through interviews, supported by the Google Forms tool, to collect testimonies that contributed to understand the presence of films at school. The analysis of the interviews shows that the presence of this artistic expression in this space causes perceptions in students, illuminates a path that enhances transformations. It is considered that pedagogical practices based on these audiovisual plots, driven by the teachers' work, as a revealing light, re-signify knowledge and reverberate in students, beyond the school space.